Meniscus Injuries in the Military Athlete - Donohue, Michael A.; Zhou, Liang; Haley, Chad A. (The Journal of Knee Surgery, 2019)
Meniscal injuries in the young, active patient are often challenging injuries for the orthopaedic surgeon whose goal is to provide pain-free return to play/military duty and preserve maximal meniscal integrity. In the U.S. military, the incidence rate of meniscal tears is almost 10 times higher than that of the civilian population; although, the rates of reoperation following meniscal repair are fairly similar. The decision to pursue meniscal debridement versus repair is multifactorial depending on tear characteristics, concomitant injury, patient characteristics, and goals. Meniscal allograft transplantation remains reserved as a salvage procedure but with limited goals for potential to return to complete unrestricted military duties. The purpose of this article is to review treatment principles for the military athlete with meniscal pathology.
Keywords: meniscus; debridement; repair; meniscectomy; knee; arthroscopy